2010
DOI: 10.1111/j.1432-2277.2010.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial impact of temporary porto-caval shunt in orthotopic liver transplantation: a single center analysis

Abstract: Summary The use of temporary porto‐caval shunt (TPCS) has been shown to improve hemodynamic stability and renal function in patients undergoing orthotopic liver transplantation (OLT). We evaluated the impact of TPCS in OLT and analyzed the differences according to model for end‐stage liver disease (MELD), donor risk index (DRI) and D‐MELD. This is a retrospective single‐center analysis of 148 consecutive OLT. Fifty‐eight OLT were performed using TPCS and 90 without TPCS. Donor and recipient data with pre‐OLT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(72 citation statements)
references
References 31 publications
1
58
0
13
Order By: Relevance
“…Equivalent surgical times have been observed between cases with and without TPCS is attributed to the time spent performing TPCS regained with an easier hepatectomy done on a fully devascularized organ, and shorter final hemostasis. 20,21 The observed frequency of cardiac arrest at reperfusion was low (3%), and occurred in the Classic and PB groups. No cardiac arrests were observed in the SS group.…”
Section: Discussionmentioning
confidence: 93%
“…Equivalent surgical times have been observed between cases with and without TPCS is attributed to the time spent performing TPCS regained with an easier hepatectomy done on a fully devascularized organ, and shorter final hemostasis. 20,21 The observed frequency of cardiac arrest at reperfusion was low (3%), and occurred in the Classic and PB groups. No cardiac arrests were observed in the SS group.…”
Section: Discussionmentioning
confidence: 93%
“…Impaired renal perfusion, vascular instability and the release of cytokines at reperfusion contribute to a reduction in renal function [102] . In a study by Ghinolfi et al [100] it has been shown to improve hemodynamic stability and renal function in patients undergoing orthotopic LT. Lower graft survival rates were reported in patients of high DRI liver grafts when a TPCS was not used [100] . TPCS improves the perioperative outcome, this being more evident when highrisk grafts are allocated to high-risk patients [100] .…”
Section: Transplantationmentioning
confidence: 99%
“…In a study by Ghinolfi et al [100] it has been shown to improve hemodynamic stability and renal function in patients undergoing orthotopic LT. Lower graft survival rates were reported in patients of high DRI liver grafts when a TPCS was not used [100] . TPCS improves the perioperative outcome, this being more evident when highrisk grafts are allocated to high-risk patients [100] . Another series by Pratschke et al [103] showed reduced hepatic injury and increased portal flow after reperfusion.…”
Section: Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Use of a temporary portocaval shunt (TPCS) has been reported to reduce the need for vasopressors, to provide better hemodynamic stability and splanchnic outflow, and to decrease the risk of postreperfusion syndrome, (4,5) with a varied benefit on graft and patient survival. (6) Such advantages may be of great importance in the setting of graft marginality like elderly donation and/or in severely compromised recipients.…”
mentioning
confidence: 99%